Translating Arabic Poetic Riddles into English: An Approach in Qualitative Studies - Omar, Nida Salim; Kadhim Al Alwan, Kais Amir; Abdul Khaliq Al-Baqoa, Mahmood (Respectus Philologicus, 2022)
A riddle is a question that usually occurs in prose and poetic form. The composition of poetic riddles is complicated since it encompasses trick structure of English utterances that require more efforts and deep thinking on the part of readers to reach the intention of the riddle maker. The present study investigated the interpretation of utterances in poetic riddles when translated into English. The main objective was to extend the tricky utterances in poetic riddles to obtain the intention of the riddle maker through translation. To achieve this target, a Relevance Theory by Sperber and Wilson (1986; 1995) was adopted to cognitively interpret how the poetic riddles worked through translation. Then, Bach’s (1994) Ambiguity was also used to explain the meaning that fell under a word, phrase or even a statement. Finally, Gutt’s (1991; 1998; 2000) notion on the directness and indirectness of the interpretation was employed. Overall, the results showed that Arabic poetic riddles included ambiguous words as well as implicit meanings that require decoding to gain the intent word made by the riddle maker. Furthermore, Arabic poetic riddles are full of attribute words to help getting the intent word.